Determinants in developing a learning factory in higher educational institution - Fatimah, Mahmud; Puteri Fadzline, Muhamad Tamyez; Mohamad Farizuan, Mohd Nor (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Manufacturing education will be faced with major challenges in the years to come. Due to the rapid changes of products and production systems, students need to be more exposed to existing and advanced methods. The purpose of this study is to examine a student’s perception toward determinants to be considered in developing a learning factory that can provide an authentic industrial working experience in the manufacturing and production sector in the higher educational institution that they are enrolled. An appropriate learning factory experience is expected to improve students’ competencies and skills. The study used quantitative method to collect the student perception on determinants of learning factory development. Two hundred questionnaires have been distributed among students of Faculty Industrial Technology Management (FIM) in Universiti Malaysia Pahang (UMP). The results of survey revealed that the most important determinant in developing the learning factory are the learning factory layout design, equipment capability, safety and the effectiveness of assessment given related with theory knowledge that has been learnt. This result is useful for the management of Faculty of Industrial Technology Management to improve their decisionmaking process in enhancing the learning factory in UMP for the future development.